A tale of two citizens: The Brey-Dano proportionality gap in UK courts and tribunals. Issue 2 (June 2021) - Hooton, Victoria E.
The role of proportionality and individual assessments in EU residency and welfare access cases has changed significantly over the course of the last decade. This article demonstrates how a search for certainty and efficiency in this area of EU law has created greater uncertainty, more legal hurdles for citizens, and less consistency in decision-making at the national level. UK case law illustrates the difficulty faced by national authorities when interpreting and applying the rules relating to welfare access and proportionality. Ultimately, the law lacks the consistency and transparency that recent CJEU case law seeks to obtain, raising the question of whether the shift from the Court's previous, more flexible, case-by-case approach was desirable after all.